Impacts of the COVID-19 pandemic on theoretical-practical teaching of nursing graduation (Research, Society and Development, 2021)
The present study aims to recognize the impacts of the pandemic on the training of undergraduate nursing students, in the first instance, in order to question and highlight the current scenario in which the students find themselves; how the impossibility of physical contact hindered laboratory and internship practices, consequently, how it affected their training, as future nursing professionals. To this end, an integrative literature review was carried out, the relevance of which is the opportunity to gather, review, update and discuss important and fashionable topics. In view of the pandemic scenario and the need for social isolation to the detriment of COVID-19, changes were necessary concerning the forms of teaching, both in undergraduate and graduate courses. In this context, there were significant limitations, both in terms of the teaching-learning process and in caring for the disease itself. In addition, it is worth noting that the modality exclusively at a distance - despite the resources in distance education - does not make it possible to supply the essential elements in care, such as direct contact, face-to-face interaction, presence; actions that have always been part of nursing. Thus, the article contributes to the dissemination of information about the topic in question, in addition to contributing to the improvement of issues aimed at offering greater quality in the professional development of new nursing professionals.